Andrea, paano ba ang maging isang ina? - Portes, Gil; Aunor, Nora; Alajar, Gina; Samartino, Lloyd; Lee, Ricardo; MRN Films (Firm). ([Pace of production not identified] MRN Films, 1990)
"Andrea is a communist insurgent who fights the government in an armed conflict. When it is time for her to give birth, she seeks refuge in the city to her best friend Joyce who is married to Emil, a guy who has no sympathy to the likes of Andrea. When Andrea's husband is reportedly killed, she temporarily leaves her son to their care. The childless couple becomes emotionally attached to her son. But before Andrea could return to her baby, she is arrested by the military. With no news of Andrea's whereabouts and presuming her to have been dead, the couple has decided to keep the child and bring him to the United States. When they return to the country after seven years for a visit, Andrea confronts them and tries to claim his son back".
"Summary taken from https://www.imdb.com/title/tt0124982/plotsummary?ref_=tt_ov_pl
Produced by Maribel Aunor and Mely Nicandro ; music by Mon Faustino; cinematography by Ely Cruz.
Nora Aunor, Gina Alajar, Lloyd Samartino.
DVD
In Tagalog.
Keywords: Drama